Elementos finitos Taylorianos - Kortchergenko, Ihor Dionisio (1976)
A finite element model which makes use of the Taylor series to represent the displacement field, is presented. This way the interpolation functions for a domain in the periphery of the origin of the expansion in series are defined in respect to some points in the periphery of that origin. The form of the element can be chosen freely, permiting to easily fallow curvilinear boundaries. The element present good characteristics to attend curvatures of the field of displacements and show beter convergence characteristics when compared with other polynomial series representation.